Internalisasi Nilai-Nilai Pendidikan Agama Islam Dalam Menumbuhkan Kesehatan Mental Siswa di SMK SULTAN AGUNG 1 TEBUIRENG JOMBANG - Iqbal Hamdani; Syamsuddin Syamsuddin (CV. KAMPUS AKADEMIK PUBLISING, 2025)
In the modern era, the moral crisis among the youth often becomes the focus of criticism toward educational institutions. Education has an important mission to shape individuals with noble character, which is the expected profile of the national education system. This study aims to examine how the internalization of Islamic Religious Education (PAI) values at SMK Sultan Agung 1 Tebuireng Jombang and its impact on students' mental health. The research employs a qualitative approach with a case study design. Data collection was conducted through observation, interviews, and documentation. The informants of the study include the principal, PAI teachers, and students. Data analysis was done using source triangulation. The findings indicate that the internalization of PAI values, such as discipline, responsibility, and respect for teachers, plays a significant role in shaping character and improving students' mental health. Religious practices such as congregational prayers, istighosah, and Quran recitation support the development of students' mental and spiritual well-being. The Islamic education applied at SMK Sultan Agung 1 Tebuireng Jombang contributes to mental resilience, emotional balance, and harmonious social relationships.